Penerapan Cleanliness Health Safety Environmental Sustainability di Sektor Pariwisata - Darmaya , I Gede; Ekasani , Kadek Ayu; Supartini , Ni Luh (Jurnal Ilmiah Pariwisata dan Bisnis, 2023)
The 101 Bali Fontana Seminyak merupakan salah satu tempat yang menyediakan akomodasi untuk berbagai kegiatan namun keberadaannya harus memberikan rasa aman dan nyaman bagi pemakainya. Melalui protokol kesehatan Cleanliness, Health, Safety,& Environmental Sustainability sektor pariwisata dan ekonomi kreatif dalam negeri dapat segera bangkit dan pulih, untuk itu Kementerian Pariwisata dan Ekonomi Kreatif telah mewajibkan semua industri pariwisata untuk menerapkan protokol Cleanliness, Health, Safety, & Environmental Sustainability. Penelitian ini bertujuan untuk mengetahui bagaimana penerapan dan f aktor – faktor yang mempengaruhi penerapan Cleanliness, Health, Safety, & Environmental Sustainability. CHSE dalam teknik pengumpulan data menggunakan metode wawancara, dokumentasi dan kuesioner. Teknik analisis data yang digunakan yaitu statistik deskriptif sehinggga diketahui nilai rata-rata penilaian tamu secara umum. Berdasarkan hasil penelitian terdapat nilai rata- rata penerapan sebesar 4,4 dengan kreteria penerapan Cleanliness, Health, Safety, & Environmental Sustainability dinyatakan sangat baik. Faktor-faktor yang mempengaruhi penerapan Cleanliness, Health, Safety,& Environmental Sustainability yaitu pembiayaan peralatan protokol kesehatan, kurangnya pendapatan serta pihak hotel mengundang PMI dan Dinas Kesehatan Kabupaten Badung bergabung dalam mensosialisasikan penerapan protokol kesehatan dan penerapan Cleanliness, Health, Safety , & Environmental Sustainability. The 101 Bali Fontana Seminyak is a place that provides accommodation for various activities but its existence must provide a sense of security and comfort for the wearer. Through the health protocol Cleanliness, Health, Safety, & Environmental Sustainability the tourism sector and the domestic creative economy can quickly rise and recover, for this reason the Ministry of Tourism and Creative Economy has made it mandatory for all tourism industries to implement the Cleanliness, Health, Safety, & Environmental Sustainability protocol. This study aims to find out how the implementation and f the factors that influence the implementation of Cleanliness, Health, Safety, & Environmental Sustainability. CHSE in data collection techniques uses interview, documentation and questionnaire methods. The data analysis technique used is descriptive statistics so that the average value of guest ratings in general is known. Based on the research results, there is an average implementation value of 4.4 with the criteria for implementing Cleanliness, Health, Safety, & Environmental Sustainability stated to be very good. Factors that influence the implementation of Cleanliness, Health, Safety, & Environmental Sustainability, namely financing for health protocol equipment, lack of income and the hotel inviting PMI and the Badung District Health Office to join in socializing the implementation of health protocols and implementing Cleanliness, Health, Safety, & Environmental Sustainability.